Activated Mangosteen shell in removal of mercury ion from aqueous solution. (2021) - Anitha, D.; Ramadevi, A.; Seetharaman, R.
Abstract: The poisonous heavy metal mercury was removed from aqueous solution using bicarbonate treated mangosteen shell a biosorbent available at low cost. Batch experiments were performed to evaluate the parameters like contact time, pH, carbon dose on the removal efficiency of Hg (II) from aqueous solution. Scanning electron microscopy and Energy-dispersive X-ray spectroscopy analysis were carried out to study the surface morphology. Removal of mercury occurs at the optimum experimental condition at pH 5 and carbon dosage of 120 mg. Adsorption isotherm was evaluated using Langmuir, Freundlich and Temkin isotherm adsorption models. The Langmuir adsorption shows Q0 value of 49.75 mg g −1 for BTMC.